Analysing the Correlation between English Proficiency and Academic Performance among Thai University Students - Matthew Rudd; Lawrence Honkiss (Athens Institute for Education and Research, 2020)
The primary objective of this research paper is to examine the relationship between students' English language proficiency skills and academic performance across unrelated subjects from a sample population totalling 2,026 students at a private university in the surrounding areas of Bangkok. Participants in this research study comprised first, second and third year students from four separate faculties: engineering, business administration, I.T and veterinary science. This study collated English language assessment results and grade point average from all participants to analyse the correlation between the two performance-related variables via t-test significance testing (0.05) and Pearson's correlation coefficient analysis. On the grounds of Spearman's "g" factor theory of intelligence, this paper worked on the theory that higher English performance outcomes would naturally translate into higher GPA attainments. The t-test results derived from quantitative data indicated that the means of the two sets of performance-related variables were significantly different (p <0.05). However, the correlation coefficient analysis revealed a highly positive relationship between English language proficiency and GPA attainments (r = 0.653), leading to the unequivocal observation that higher English proficiency levels were associated with higher standards of GPA across all measures; (1) year group, (2) gender, (3) faculty, and (4) the entire sample population.